PENGEMBANGAN FISIK MOTORIK ANAK USIA DINI DENGAN BERMAI - Farhatin Masruroh; Khulusinniyah Khulusinniyah (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
The first five years of a children’s age is the period of rapid growth with physical and motor development. Those process will develop well if stimulated continuously. Early childhood always identic with high activity requires the opportunity to express their abilities. Therefore playing method is very urgent inchildren’s gross motor skills and fine motor skills development through a variety of playing activities both indoors and outdoors. Playing is an activity that cannot be separated from early childhood’s world. All playing activities will be carried out happily. By the same token learning by playing will be done happily without any sense of being forced or oppressed.